Tradisi Pesta Pembagian Zakat di Kenagarian Barung-Barung Balantai Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan 1970-2005 - Hoktaviandri Hoktaviandri (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
The implementation of the zakat distribution party is done at the house of the tithe. The person who receives zakat is the person who is invited by the tithe person. Zakat is divided equally, not distributed to the person who has the right to receive it, the person invited and come he gets a portion of the treasured property, both poor and rich, both entitled and not entitled, still receive the zakat. Zakat is distributed at a party agreed upon by mamak. The purpose of writing in this paper is to find the history of the birth of a zakat distribution party in Kenagarian Barung-Barung Balantai, to describe how the tradition of zakat distribution parties in Kenagarian Barung-Barung Balantai, to know the development of the tradition of the zakat distribution party 1970-2005 in Kenagarian Barung-Barung Balantai and need to be preserved, to explain the factors that motivate the community to maintain the tradition of zakat distribution parties in Kenagarian Barung-Barung Balantai. The approach used is the hitoris approach. The findings obtained from this study indicate that the tradition of the zakat distribution party carried out by the Kenagarian Barung-Barung Balantai community was due to the desire of the community to implement the Islamic Shari'ah and broadcast it called the Islamic da'wah, the relationship of their fellow human beings, motivating the nomads to return to hometown and in this tradition many contain positive values ??and do not conflict with the teachings of Islam.